Rezension von: Taddey, Gerhard; Fischer, Joachim (Hrsg.), Lebensbilder aus Baden-Württemberg. Band 20 - Stihler, Daniel (Württembergisch Franken, 2003)
Gerhard Taddey, Joachim Fischer (Hrsgg.); Lebensbilder aus Baden-Württemberg, Bd. 20, Stuttgart (W. Kohlhammer) 2001, 529 S., Abb.